Efektifitas Penggunaan Flash Video Dalam Meningkatkan Ketrampilan Istima’ Mufrodat Siswa Kelas VII di Madrasah Tsanawiyyah Nahdlotul ‘Ulama Berbek Waru Sidoarjo : Efektifitas Penggunaan Flash Video Dalam Meningkatkan Ketrampilan Istima’ Mufrodat Siswa Sidoarjo - Faruq Abdul Muid; Abdussalam (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2021)
The development of technology that exists today cannot be denied its influence in the field of education. The computerization of learning media is already familiar. One of the popular learning media is flash video. The use of flash videos is expected to be able to attract more students' attention in the learning process and also make it easier for students to understand the lesson. Listening skills as the basis of language acquisition is one of the important points that must be considered by Arabic language teachers, most of whom pay little attention to this. This study was aimed to determine the effectiveness of flash video media in improving students' vocabulary listening skills. This research was conducted at MTs NU Berbek Waru Sidoarjo using quantitative research methods. The formulation of the problem from this research is as follows: 1. How is the istima' mufrodat skill of class VII students at the madrasah Tsanawiyyah nahdlotul 'ulama with waru sidoarjo?. How is the effectiveness of using "video flash" learning media in improving the special skills of class VII students at Madrasah Tsanawiyyah Nahdlotul 'Ulama Berbek Waru Sidoarjo. Data were collected by conducting pre-test and post-test to class VII students and interviews. The use of flash video media was welcomed by students and was proven by an increase in student learning outcomes after comparing the pre-test and post-test scores and analyzed using the "t" test with an error significance level of 0.05 with a value of 2.281, thus Ho is rejected. . In other words, the use of "flash video" learning media is effective in improving students' special skills. Therefore, this media should be developed and used in the teaching and learning process of Arabic in schools.